Organic Nanostructures: Light‐Assisted Charge Propagation in Networks of Organic Semiconductor Crystallites on Hexagonal Boron Nitride (Adv. Funct. Mater. 43/2019). (22nd October 2019) - Matković, Aleksandar; Genser, Jakob; Kratzer, Markus; Lüftner, Daniel; Chen, Zhongrui; Siri, Olivier; Puschnig, Peter; Becker, Conrad; Teichert, Christian
Abstract : In article number1903816, Aleksandar Matković and co‐workers employ networks of self‐assembled organic nanostructures epitaxially grown on two‐dimensional hexagonal boron nitride. The work demonstrates how the polarization direction of external light can be used to realize a "light‐gate" for switching on and off the conductivity of organic nanocrystals, and to even guide charge propagation along desired directions in self‐assembled crystallite networks.